\(A=x^2+2y^2+2xy+2x-4y+2016\)
\(=x^2+y^2+y^2+2xy+2x+2y-6y+2016\)
\(=\left(x^2+2xy+y^2\right)+\left(y^2-6y+9\right)+\left(2x+2y\right)+2007\)
\(=\left(x+y\right)^2+\left(y-3\right)^2+2\left(x+y\right)+2007\)
\(=\left(x+y+1\right)^2+\left(y-3\right)^2+2006\)
Vì \(\hept{\begin{cases}\left(x+y+1\right)^2\ge0;\forall x,y\\\left(y-3\right)^2\ge0;\forall x,y\end{cases}}\)\(\Rightarrow\left(x+y+1\right)^2+\left(y-3\right)^2\ge0;\forall x,y\)
\(\Rightarrow\left(x+y+1\right)^2+\left(y-3\right)^2+2006\ge0+2006;\forall x,y\)
Hay \(A\ge2006;\forall x,y\)
Dấu"=" xảy ra \(\Leftrightarrow\hept{\begin{cases}\left(x+y+1\right)^2=0\\\left(y-3\right)^2=0\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}x=2\\y=3\end{cases}}\)
Vậy \(A_{min}=2006\)\(\Leftrightarrow\hept{\begin{cases}x=2\\y=3\end{cases}}\)